2013
DOI: 10.5851/kosfa.2013.33.6.744
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Kefir Manufactured by a Two-Step Fermentation

Abstract: The objective of this study was to assess the physicochemical and sensory changes of a kefir manufactured by a two-step fermentation (MTY, 1 st step: 37 o C for 9 h; 2 nd step: 24 o C for 15 h) and compare it with kefirs produced by two conventional methods (GTY, fermentation at 37 o C for 24 h; KEY, 22 o C for 24 h). Rapid changes in pH and titratable acidity (TA) were observed in samples from all three manufacturing methods during fermentation process and storage period. Lactic acid bacteria (LAB) counts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
6
7
0
2
Order By: Relevance
“…The number of LABs during storage did not change significantly. Similar results were reported in Yoo et al (2013) as well. Kang et al (2013) reported that the number of LABs did not change much during storage for 9 days.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The number of LABs during storage did not change significantly. Similar results were reported in Yoo et al (2013) as well. Kang et al (2013) reported that the number of LABs did not change much during storage for 9 days.…”
Section: Discussionsupporting
confidence: 91%
“…There was no significant difference in bacterial inoculated samples either. Similar results were obtained from Yoo et al (2013). On another study, Özdestan & Üren (2010) reported that pH values changed between 4.11 and 4.53 in the kefir samples and the TA values varied between 0.65% and 1.05%.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The pH and TA values found in this study are considered to be in the acceptable range of a commercial yogurt (Kang et al, 2013). These results for kefir are in agreement with the findings of Yoo et al, (2013).…”
Section: Resultssupporting
confidence: 90%